COMPARATIVE STUDY OF THEORETICAL AND FIELD DATA ON SOIL SETTLEMENT PLAZA SUMMARECON BANUNG CASE STUDY - Aldi Rachman Pamungkas; Moch. Sholeh (Jurusan Teknik Sipil Politeknik Negeri Malang, 2026)
This research investigates the discrepancy between theoretical and actual field settlement in soft clay soils, using the Plaza Summarecon Bandung project as a case study. Soil improvement techniques involving preloading and the installation of Prefabricated Vertical Drains (PVD) and Prefabricated Horizontal Drains (PHD) were applied to accelerate consolidation and enhance soil stability. The objective of this study is to compare theoretical settlement calculations with actual field measurements, identify contributing factors to discrepancies, and propose refinements to the theoretical models. The research method involves collecting soil investigation data, field monitoring data (Settlement Plates), and project construction documentation. Theoretical settlement was calculated using Terzaghi’s one-dimensional consolidation theory and extended with Barron and Hansbo's PVD acceleration models. Field settlement data were analyzed over time to create settlement curves and evaluate actual behavior during the preloading period. Findings show that actual settlement significantly deviates from theoretical predictions. The settlement prediction accuracy for Settlement Plate (SP) 1 is 25.43%, SP-2 is 46.97%, and SP-3 is 94.40%. The deviation is primarily due to incomplete soil investigation data, omission of construction and indirect loads in theoretical models, and inconsistencies in field monitoring. Additionally, differences in PVD patterns (triangular vs. square) affected the time to 90% consolidation, with triangular layouts achieving faster results due to better service area coverage. This study concludes that theoretical models can be refined by incorporating site-specific factors, adhering to standard soil investigation protocols, and improving field monitoring practices. It emphasizes the importance of accurate modeling and continuous instrumentation for ensuring reliable ground improvement in soft soil areas.